SELECTION OF THE RIGHT MARKETPLACE FOR SALE OF ORNAMENTAL PLANTS USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD - Syarif Hidayat HR; Melan Susanti; Mari Rahmawati (Jurnal Techno Nusa Mandiri, 2021)
Basically, each marketplace has its own market, therefore as a seller who will start an online business, especially those who use the marketplace, they must know which marketplace is right to start their online business according to what category of goods to sell. This research is needed to help business people, in this case ornamental plant traders, choose the right marketplace for their online business activities. Decision Support System (DSS) is a computer-based system used to help make decisions from structured and semi-structured problems. Analytical Hierarchy Process (AHP) is a method that can be used to select from the specified criteria. This method can simplify the criteria that are considered in making decisions for marketplace selection to be simpler and easier to understand. The results of the study show that the decisions made using the AHP method are very effective, and are expected to help make objective decisions. After processing data and analyzing respondent data, with the criteria for the number of visitors, transaction system, features, and searc engine optimization (SEO), it was found that Lazada (0.428) has the highest priority, Tokopedia (0.235) with second priority, Shopee (0.204) with priority third, and Bukalapak (0.133) with the fourth priority